Air Force operational test and training infrastructure barriers to full implementation - Toukan, Mark; Walsh, Matthew; Kochhar, Ajay K.; Yonekura, Emmi; Schulker, David (RAND, 2022)
Senior leaders on the Joint Staff are becoming increasingly concerned that the readiness assessment system is unable to provide credible answers to whether U.S. air forces can meet the demands of high-end conflict and whether individuals and aircrews have developed the right skills to complete their missions in stressful, complex environments. The sense is that the emphasis has not been on possible future scenarios and that readiness metrics do not provide accurate signals of force deficiencies. This ultimately results in decision priorities that do not align with national strategy. This report focuses on the Air Force's operational test and training infrastructure (OTTI), which is responsible for achieving aircrew readiness, and on the processes for assessing skill development and maintenance. The authors further focus on OTTI for the combat air forces. The objective was to offer diverse stakeholders a framework they can use to easily discern the implications of different training infrastructure investments for assessing skills and monitoring readiness. The authors describe interdependencies across different components of OTTI and implications for coordinating and prioritizing investments in those components
Keywords: United States / Air Force / Airmen / Training of; United States / Air Force / Operational readiness; United States / Air Force / Combat sustainability; United States / Air Force / Officers / Training of; Combat sustainability (Military science) / United States; Operational readiness (Military science); États-Unis / Air Force / État de préparation opérationnelle; États-Unis / Air Force / Officiers / Formation; État de préparation opérationnelle (Science militaire)